OpenStreetMap in GIScience: Experiences, Research, and Applications - Jokar Arsanjani, Jamal (Springer, 2015)
An Introduction to OpenStreetMap in Geographic Information Science: Experiences, Research, and Applications -- Assessment of logical consistency in OpenStreetMap based on the spatial similarity concept -- Quality assessment of the contributed land use information from OpenStreetMap versus authoritative datasets -- Improving volunteered geographic information quality using a tag recommender system: The case of OpenStreetMap -- Inferring the Scale of OpenStreetMap Features -- Data retrieval for small spatial regions in OpenStreetMap -- The Impact of Society on Volunteered Geographic Information: The case of OpenStreetMap -- Social and political dimensions of the OpenStreetMap project: Towards a critical geographical research agenda -- Spatial Collaboration Networks of OpenStreetMap -- Route choice analysis of urban cycling behaviors using OpenStreetMap: Evidence from a British urban environment -- The Next Generation of Navigational Services using OpenStreetMap data: the Integration of Augmented Reality and Graph Databases -- Building a Multimodal Urban Network Model Using OpenStreetMap Data for the Analysis of Sustainable Accessibility -- Assessing OpenStreetMap as an Open Property Map -- Investigating the Potential of OpenStreetMap for Land Use/Land Cover Production: A Case Study for Continental Portugal -- Using Crowd-Sourced Data to Quantify the Complex Urban Fabric – OpenStreetMap and the Urban–Rural Index.
Includes bibliographical references
Vendor-supplied metadata
Keywords: OpenStreetMap; Geoinformation